The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1055/s-2002-35956
|View full text |Cite
|
Sign up to set email alerts
|

In Hydronephrosis Less than 10 % Kidney Function is not an Indication for Nephrectomy in Children

Abstract: Contrary to common practice we do not recommend nephrectomy for hydronephrotic kidneys which show < 10 % of renal function on renogram. The renal functional status improves significantly after a preliminary nephrostomy, thus avoiding the need for a straightforward nephrectomy in children along with all the possible long-term effects of a single kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 5 publications
2
30
0
3
Order By: Relevance
“…However, dynamic renography may not reflect the true renal function in patients affected by severe hydronephrosis. This may contribute directly to the gradual increase in pressure in the renal pelvis [3], which may in turn prevent the absorption of the radionuclide imaging agent by the kidney, suggesting low renal function. Isoyama et al [13] also found that, although preoperative diuretic renography showed a non-functional kidney, renal function was remarkably improved postoperatively in some patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, dynamic renography may not reflect the true renal function in patients affected by severe hydronephrosis. This may contribute directly to the gradual increase in pressure in the renal pelvis [3], which may in turn prevent the absorption of the radionuclide imaging agent by the kidney, suggesting low renal function. Isoyama et al [13] also found that, although preoperative diuretic renography showed a non-functional kidney, renal function was remarkably improved postoperatively in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hydronephrosis in infants and children is often associated with a short disease duration and only mildly impaired renal function. Furthermore, the kidneys are still developing in infants and children, allowing the potential for this organ to regain its normal function after timely relief from any obstruction [3,4]. However, kidneys in adults are fully developed, and the factors affecting the recoverability of renal function after surgery in adults with UPJO remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actuellement, on considère qu'un rein peut-être conservé si sa valeur fonctionnelle relative est supérieure à 10%, voire moins selon les travaux de Aziz et al; car de fait, il n'existe pas de corrélation entre l'importance de la dilatation et le degré d'obstruction [8,9]. Ainsi, une cure chirurgicale de désobstruction, type pyéloplastie, peut être envisagée pour les hydronéphrose géantes sur SJPU.…”
Section: Discussionunclassified
“…40 Ponekad je pre nefrektomije potrebno postaviti perkutanu nefrostomu i posmatrati ponašanje parenhima nakon uklanjanja opstrukcije. 40,58 Nefrektomija se predlaže i u slučajevima često ponavljanih epizoda urinarne infekcije kod izražene hidronefroze, u slučajevima multiple kalkuloze i u slučajevima hipertenzije.…”
unclassified